PERAN KANTOR URUSAN AGAMA DALAM MEMINIMALISIR RESEPSI PERNIKAHAN PADA MASA PANDEMI COVID-19 - Astri Fuji; Qadir Gassing; Hadi Daeng Mapuna (Universitas Islam Negeri Alauddin Makassar)
The main problem in this study is the Role of the Office of Religious Affairs in Minimizing Wedding Receptions During the Covid-19 Pandemic (Case Study in Manggala District, Antang, Makassar City). The main problem is divided into two sub-problems: 1. What is the level of development of wedding receptions in Manggala District, Antang Makassar City during the Covid-19 pandemic? 2. How is the community's response to the role of KUA in Manggala District, Antang Makassar City in minimizing wedding receptions? Descriptive Qualitative Research is the type of research used in this paper, namely in the form of field research. The sources of data for this research are the surrounding community who have held wedding receptions during the Covid-19 pandemic and resource persons related to the title of the study. Data collection methods used are observation, interviews and documentation. The results of the study, the wedding reception is a form of self-existence by the Bugis Makassar custom which is still maintained in the community. The implications of this study: 1) The person who will conduct the wedding reception first consults or communicates with the village priest, head of KUA or local government to find out what is allowed and not allowed in the event. 2) The couple or family concerned who want to get married and plan to hold a reception must meet the health protocol requirements, so that the reception runs smoothly and wisely. Keywords: Wedding, Reception, Covid-19 Pandemic.